Effect of the Push-up Plus (PUP) Exercise at Different Shoulder Rotation Angles on Shoulder Muscle Activities - Cho, Sung-Hak (J Phys Ther Sci, 2014)
[Purpose] Although the Push-Up Plus is a useful exercise method for shoulder stabilization, few studies have examined its effects at different angles of shoulder rotation. Therefore, the present study investigated the most effective exercise method for shoulder stabilization by analyzing muscle activities of the rotator cuff muscles at different angles of shoulder rotation. [Subjects] Fifteen healthy university students in their 20s were the subjects of this study. [Methods] Changes in muscle EMG related to shoulder stabilization were analyzed by performing the Push-Up Plus in shoulder positions of neutral, internal and external rotation. [Results] The highest muscle activity was found in external rotation, and in internal rotation the pectoralis major and levator scapula showed significantly lower activities than the other positions. [Conclusion] Selectively changing the rotation angle of the shoulder for different purposes of the shoulder exercise would be an effective exercise method.